Secrets of Sloane House - Gray, Shelley (Thorndike, Maine : Center Point Large Print, 2014)
"One woman's search for the truth of her sister's disappearance leads her to deceit and danger in 1893 Chicago"--
Keywords: Family secrets -- Fiction; Large type books; Mystery fiction; Christian fiction